2015
DOI: 10.1158/1538-7445.am2015-4101
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4101: Clinical significance of ZEB1 mRNA levels in peritoneal washing for gastric cancer

Abstract: Backgrounds. ZEB1 affects cancer progression by regulating Epithelial to mesenchymal transition (EMT) in some cancers. In gastric cancer, ZEB1 expression in cancer tissue has been identified as an independent prognostic factor. We also reported on a significant correlation between ZEB1 expression and diffuse phenotype in gastric cancer, and that patients with high ZEB1 expression had significantly poorer survival than those with low expression. It was also reported that ZEB1 was an independent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been suggested that ZEB proteins are highly expressed in many cancer cells including GC cells [35][36][37][38][39]. In addition, ZEB1 was identified as an independent prognostic factor of GC, and there is a significant correlation between ZEB1 expression and diffuse phenotype in GC [38]. Previous studies suggested that a variety of factors such as microRNAs (miRNAs) and ubiquitin ligase CUL4A can regulate the EMT process by modulating ZEB1 expression [40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that ZEB proteins are highly expressed in many cancer cells including GC cells [35][36][37][38][39]. In addition, ZEB1 was identified as an independent prognostic factor of GC, and there is a significant correlation between ZEB1 expression and diffuse phenotype in GC [38]. Previous studies suggested that a variety of factors such as microRNAs (miRNAs) and ubiquitin ligase CUL4A can regulate the EMT process by modulating ZEB1 expression [40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%